Optic disc detection and segmentation using saliency mask in retinal fundus images. (November 2022) - Zaaboub, Nihal; Sandid, Faten; Douik, Ali; Solaiman, Basel
Abstract: Background and objective: Detection of the Optic Disc (OD) in retinal fundus image is crucial in identifying diverse abnormal conditions in the retina such as diabetic retinopathy. Previous systems are oriented to the OD detection and segmentation. Most research failed to locate the OD in the case when the image does not have a criterion appearance. The objective of the proposed work is to precisely define a new and robust OD segmentation in color retinal fundus images. Methods: The proposed algorithm is composed of two stages: OD localization and segmentation. The first phase consists in the OD localization through: 1) a preprocessing step; 2) vessel extraction and elimination, and 3) a geometric analysis allowing to decide the OD location. For the second phase, a set of is computed in order to produce various candidates. A combination of these candidates accurately forms a completed contour of the OD. Results: The proposed method is evaluated using 10 publicly available databases as well as a local database. Accuracy rates in the RimOne and IDRID databases are 98.06% and 99.71%, respectively, and 100% for the Chase, Drive, HRF, Drishti, Drions, Bin Rushed, Magrabia, Messidor and LocalDB databases with an overall success rate of 99.80% and specificity rates of 99.44%, 99.64%, 99.66%, 99.66%, 99.70%, 99.87%, 99.72%, 99.83% and 99.82% for the Rim One, Drions, IDRID, Drishti, HRF, Bin Rushed, Magrabia, Messidor and proprietary databases. Conclusion: The main advantage of the proposed approach is the robustness and the excellent performances even with critical cases of retinal images. The proposed method achieves the state-of-the-art performances with regards to the OD detection and segmentation. It is also of a great interest for clinical usage without the expert intervention to treat each image. Highlights: Optic disc localization in fundus color retinal images based on novel saliency map. Novel blood vessel extraction and inpainting methods from two color channels through morphological operation and thresholding technique. Optic disc segmentation method based on multiple novel saliency maps. Implementation of various databases: ChaseDB1, Drive, HRD, Drishti, Drions, Rim-One, IDRID, Bin Rushed, Magrabi, Messidor and a local database. The proposed methods of optic disc localization and segmentation yield an overall accuracy of 99.80% and 99.63%, respectively, on 2.050 images.